PENGARUH LAJU PERTUMBUHAN PENDUDUK DAN RASIO KETERGANTUNGAN PENDUDUK SERTA PENYERAPAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT DALAM MENYONGSONG BONUS DEMOGRAFI - B01111074, Ratna Nurmala (Jurnal Pembangunan dan Pemerataan, 2016)
This research is entitiled â€œThe Influence of Population Growht Rate,Dependency Ratio, and Manpower Absorption on the Economic Growth ofRegencies/ Cities of West Kalimantan Province toward Demographic Bonusâ€.The research aimed to find out the Influence of population Growth Rate,Dependency Ratio and Manpower Absorptionn onthe Economic Growth ofRegencies/ Cities of West Kalimantan Province.The research employed a quantitative descriptive method using secondarydata i.e. panel data (cross section and time series) with the approach of pooledEGLS (Cross-section weights). The observations of the data were conducted 56times on 14 Regencies / Cities in west Kalimantan Province during the period of2009-2012.The result of the research indicated that the rate of population growth ratehad a positive and significant influence on the economic growth; populationdependency ratio had a negative and insignificant influence on the economicgrowth; Manpower Absorption had a positive and significant influence on theeconomic growth in West Kaliamantan Province.Keyword: Population Growht Rate, Population Dependency Ratio, ManpowerAbsorption and Economic Growth